Візуалізація в українській курйозній поезії раннього бароко - Литвин, Л. (Сiверянський літопис, 2025)
Однією з барокових рис є синтез мистецтв, що прослідковується в курйозній поезії, структура якої увібрала в себе засоби візуалізації. Фігурні вірші – прикметна риса літератури раннього бароко. Спираючись на стійку середньовічну візантійську культурну традицію, ренесансні впливи, поети розпочинали власну практику створення візуальної поезії. Мета статті – дослідити українські ранньобарокові вірші, у яких використано форму азбучного вірша й акровірша як структури, установити їхній зв’язок із гімнографією та латиномовною поезією. Наукова новизна: учинено спробу діахронічного аналізу засобів візуалізації ранньобарокової курйозної поезії в Україні. Уперше виснувано, що в системі жанрів зорової курйозної поезії цього часу найбільше використовувалися алфавітні вірші та акровірші; дослідився зв’язок структури цих різновидів візуальних силабічних віршів із біблійною гімнографічною поезією. Методи дослідження: комплексний підхід до аналізованого матеріалу забезпечений поєднанням інтертекстуального, культурно-історичного, описово-аналітичного й типологічного методів. Висновки: у перебігу діахронічного аналізу засобів візуалізації ранньобарокової курйозної поезії в Україні установлено, що найбільше використовувалися алфавітні вірші й акровірші. Особливості будови віршового рядка молитовного вірша передбачали акцент на початку рядка (букві чи слові). Дослідився зв’язок структури цих різновидів візуальних силабічних віршів із біблійною гімнографічною поезією. На тлі розвитку освіти та книгодрукування формування барокового світовідчуття поетів було спроєктоване на світське життя, у якому використовувалася давня поетична традиція. One of the distinct baroque features is the synthesis of art, which evidently stems from curious poetry, whose structure involves several means of visualization. Figurative poetry is an outstanding feature of the literature of the early Baroque era. Poets who founded their own practice of creating concrete poetry relied on traditional Byzantine culture as well as the influence of the Renaissance. The purpose of the publication is to examine Ukrainian poetry of the early Baroque era, which used the alphabet poetry form and acrostic as the structure, and trace its relatability to hymnology and poetry in the Latin language. The scientific novelty lies in the efforts of diachronic analysis of means of visualization of curious poetry in its early period in Ukraine. For the first time, it was found that in the system of genres of visual curiosity poetry of this time, alphabetic verses and acrostic verses were most often used; the connection between the structure of these types of visual silabic verses and biblical hymnographic poetry was investigated. Research methods rely on a comprehensive approach to the analyzed material provided with a combination of intertextual, culturally historical, descriptively analytical, and typological methods. The conclusion states that in the course of diachronic analysis of visualization means, the predominant usage of alphabet poetry and acrostics was discovered. The distinct features of the structure of poetic lines of prayer poems provided for the emphasis on the beginning of the line of the poem, a letter or a word. The examination of the relatability of the structure of these types of visually syllabic poems to biblical and hymnographic poetry took place as well. In the context of development, education, and book publishing the formation of the Baroque worldview was aimed at the secular life, which manifested the demand for ancient poetical tradition.